1995
DOI: 10.1074/jbc.270.40.23754
|View full text |Cite
|
Sign up to set email alerts
|

Saturation Mutagenesis of Human Interleukin-3

Abstract: A deletion variant of human interleukin-3, hIL-3 15-125 , was produced in the periplasmic space of Escherichia coli and had full activity in an AML193.1.3 cell proliferation assay. Libraries of random single-amino acid substitutions were constructed at each of 105 positions in the gene for hIL-3 . Approximately eight single-site substitutions at each position were produced in osmotic shock fractions and screened for activity. 15 mutants were found with bioactivity of 5-26-fold greater than that of native hIL-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
57
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 47 publications
(62 citation statements)
references
References 58 publications
5
57
0
Order By: Relevance
“…Active hIL-3 variants can be presented on phage, 14,15 and hIL-3 variants with 10-fold increased proliferative activity isolated by conventional mutagenesis have 20-fold enhanced affinity for the receptor complex. 32,40 Thus, display of native hIL-3 on phage is feasible, affinity maturation for the receptor complex could have identified variants with better agonist activities. There may be other cytokines, some perhaps unknown, that could be productively affinity matured.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Active hIL-3 variants can be presented on phage, 14,15 and hIL-3 variants with 10-fold increased proliferative activity isolated by conventional mutagenesis have 20-fold enhanced affinity for the receptor complex. 32,40 Thus, display of native hIL-3 on phage is feasible, affinity maturation for the receptor complex could have identified variants with better agonist activities. There may be other cytokines, some perhaps unknown, that could be productively affinity matured.…”
Section: Discussionmentioning
confidence: 99%
“…31 Protein variants expressed from each distinct myelopoietin variant gene were further characterized. Individual variant myelopoietin proteins were produced in E. coli as described 32 and quantitated using a sandwich ELISA for the hIL-3 receptor agonist domain. 1,14 Quantitation using the hIL-3 agonist domain was chosen to avoid artifacts due to variability in antibody recognition that could potentially occur due to mutagenic changes in the hG-CSF receptor agonist domain.…”
Section: Characterization Of Selected Variant Myelopoietin Moleculesmentioning
confidence: 99%
“…PIXY321 joins a no adverse effect is expected. Specific mutations in the C-terminal region of rhu-IL-3 have no effect on the activity [36,37]. A group of human proteins including insulin, factor VII and GM-CSF that have successfully used S. cerevisiae as a host for indusvariant molecule lacking the last eight residues has the same biological activity as the original IL-3 molecule [38].…”
Section: (Cmcys) the Glycosylated Counterparts Of This Fragment Elutedmentioning
confidence: 99%
“…14,24 Employment of a combinatorial mutagenesis strategy of the human IL-3 molecule resulted in several analogs exhibiting increased proliferative activity and hematopoietic potency relative to native IL-3. [25][26][27] Recently, it has been shown that the addition of daniplestim, one of these potent IL-3 receptor agonists, to ex vivo CD34 + cell cultures resulted in a greater increase in granulopoietic post-progenitor cells, suggesting that IL-3 receptor agonists can synergize with other lineage-specific cytokines in promoting expansion and differentiation of CD34 + cells. 28 Studies conducted in non-human primate models have demonstrated that daniplestim can potentiate the in vivo effects of rhG-CSF on mobilization of progenitor cells and neutrophil restoration, and can also prevent thrombocytopenia.…”
Section: Introductionmentioning
confidence: 99%